Benzene steam reforming kinetics in biomass gasification gas cleaning. (15th October 2016) - Kaisalo, Noora; Simell, Pekka; Lehtonen, Juha
Highlights: Effect of gasification product compounds on steam reforming of benzene was studied. H2 decelerate and CO2 accelerate the reforming kinetics. The acceleration by CO2 could not be explained only by simultaneous dry reforming. Langmuir-Hinshelwood model described air gasification gas reasonably well. Abstract: Benzene steam reforming kinetics was studied in conditions relevant to biomass gasification gas cleaning on Ni/Al2 O3 catalyst i.e. temperature range 750–900 °C and in presence of H2 S. The benzene concentration was 600–3500 ppm. The qualitative effect of the main gasification product gas compounds on the benzene steam reforming kinetics was studied. The first order kinetic model in respect to benzene was used to compare the effect of H2, CO and CO2 . It was observed that especially H2 decelerated and CO2 accelerated the benzene steam reforming kinetics. With a gas mixture representing air gasification gas, the Langmuir-Hinshelwood type model taking account effect of H2 in denominator described the benzene decomposition well. However, the model did not describe the kinetics of benzene steam reforming for the gas representing O2 /H2 O gasification gas.